Diagnosis of 'possible' mitochondrial disease: an existential crisis. Issue 3 (25th January 2019) - Parikh, Sumit; Karaa, Amel; Goldstein, Amy; Bertini, Enrico Silvio; Chinnery, Patrick F; Christodoulou, John; Cohen, Bruce H; Davis, Ryan L; Falk, Marni J; Fratter, Carl; Horvath, Rita; Koenig, Mary Kay; et al.
Abstract : Primary genetic mitochondrial diseases are often difficult to diagnose, and the term 'possible' mitochondrial disease is used frequently by clinicians when such a diagnosis is suspected. There are now many known phenocopies of mitochondrial disease. Advances in genomic testing have shown that some patients with a clinical phenotype and biochemical abnormalities suggesting mitochondrial disease may have other genetic disorders. In instances when a genetic diagnosis cannot be confirmed, a diagnosis of 'possible' mitochondrial disease may result in harm to patients and their families, creating anxiety, delaying appropriate diagnosis and leading to inappropriate management or care. A categorisation of 'diagnosis uncertain', together with a specific description of the metabolic or genetic abnormalities identified, is preferred when a mitochondrial disease cannot be genetically confirmed.